ChemInform Abstract: Reductive Etherification of Fatty Acids or Esters with Alcohols Using Molecular Hydrogen. Issue 45 (October 2016) - Erb, Benjamin; Risto, Eugen; Wendling, Timo; Goossen, Lukas J.
Abstract: The environmentally benign, robust, solvent‐free conditions render the protocol attractive for the title transformation of complex molecules.